The Influence of Religiosity and Social and Psychological Factors on Purchase Decisions and Consumer Loyalty - Ginting, Yanti Mayasari; Handriano, Rory; Sutomo (Divisi Riset, Lembaga Mitra Solusi Teknologi Informasi (L-MSTI), 2025)
This study is based on the impact of religiosity, data from social aspects, psychological factors influence how to make a purchase or what influences consumer perception and brand loyalty.In a competitive market, companies need to understand these various influences in order to draw up new marketing strategies.Religious motivation is also very important in buying decisions, for example this thing